Trust Sebagai Pemediasi Pengaruh Service Quality dan Brand Image Terhadap Repurchase Intention Pada Pengguna E-Marketplace di Provinsi Bali - Ida Bagus Wiwekananda; Ida Bagus Udayana Putra; Ni Luh Putu Indiani (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2024)
The aim of this research is to analyze the influence of service quality and brand image on repurchase intention with trust as a mediating variable among e-marketplace users in Bali Province. The method used in the research is quantitative with a questionnaire carried out systematically in accordance with the research objectives. The population in this research is the people of Bali Province who have used e-marketplaces for online shopping with a total of 130 respondents. This research uses 5 Likert scales to measure variables when testing the validity and reliability of variables. This research was analyzed using PLS-based SEM. The research results show that (1) Service quality has a positive and significant effect on repurchase intention (2) Brand image has a positive and significant effect on repurchase intention (3) Trust has a positive and significant effect on repurchase intention (4) Service quality has a positive and significant effect on trust (5) Brand image has a positive and significant effect on trust (6) Service quality has a significant effect on repurchase intention through trust (7) Brand image has a significant effect on repurchase intention through trust. It is recommended that future researchers add alternative constructs that influence repurchase intention such as customer satisfaction, e-WOM, price, promotions, etc. as well as increasing references related to research.